Layered composite fluorescent ceramic chip, preparation method thereof and luminescent device
By using the layered composite fluorescent ceramic sheet formed by MgAl2O4 transparent ceramic substrate layer and phosphor, the problem of poor thermal stability of high-power LED packaging materials is solved, and higher luminous intensity and stability are achieved, and service life is extended.
Patent Information
- Application Number
- CN202510086152.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-22
AI Technical Summary
The existing high-power LED packaging materials have poor thermal stability, resulting in short service life and low thermal conductivity of fluorescent glass, resulting in poor luminescence saturation and optical performance.
Transparent ceramic made of MgAl2O4 is used as the substrate layer, with a refractive index of about 1.71, high thermal conductivity and high temperature resistance, and combined with phosphor to form a layered composite fluorescent ceramic sheet, which is used for packaging of high-power LEDs.
It improves the luminous intensity and stability of LEDs, extends service life, reduces chip temperature, and enhances the thermal stability and optical performance of the package.
Smart Images

Figure CN119858360A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of LED luminescence, and in particular relates to a layered composite fluorescent ceramic sheet and a preparation method thereof, and a luminescent device. Background Art
[0002] High-power LED is a light-emitting diode with a higher rated working power. It is based on the principle of semiconductor PN junction light emission. When a forward voltage is applied to both ends of the chip, positive and negative charges recombine in the PN junction area and release energy, thereby generating photons. Compared with traditional lighting sources, high-power LED has higher brightness, lower energy consumption, longer service life and better environmental performance.
[0003] White light LED (W-LED) is a new type of solid-state lighting technology. It has attracted widespread attention due to its high luminous efficiency, long service life and low power consumption. There are currently two main types of white light LED packaging conversion technologies on the market. The first is a ceramic substrate combined with phosphor glue (Phosphorinsilicone, PiS); the second is a ceramic substrate combined with phosphor glass (Phosphoringlass, PiG). The mainstream white light LED packaging method is phosphor glue packaging, but the poor thermal stability of the phosphor and the aging of the packaging material lead to a short service life. Therefore, for high-power LEDs, the use of packaging materials with fast heat dissipation and high thermal stability is the key to improving the life of the LED. Phosphor glass has great advantages in preparation cost, large-scale production and color scalability, but its thermal conductivity is low (about 1W·m -1 ·K -1 ) is prone to luminescence saturation at low power density, and the refractive index of the glass matrix (about 1.5) does not match the refractive index of YAG:Ce (about 1.84), resulting in low transparency and poor optical performance of the material. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a layered composite fluorescent ceramic sheet and a preparation method thereof and a light-emitting device. 2 O 4 The transparent ceramic material is used as the substrate layer, with a refractive index of about 1.71, and high light extraction efficiency. 2 O 4 Transparent ceramics are light-transmitting and resistant to high temperatures, with a high thermal conductivity (17.0 W / m·K), which helps lower the operating temperature of fluorescent materials, thereby lowering chip temperature, increasing operating current, and further enhancing the stability and luminous intensity of high-power LEDs. By stacking multiple layers of fluorescent ceramic layers in sequence on a transparent ceramic substrate, a layered composite fluorescent ceramic sheet is formed.
[0005] The present invention solves the above technical problems through the following technical solutions.
[0006] The first object of the present invention is to provide a layered composite fluorescent ceramic sheet, the layered composite fluorescent ceramic sheet comprises a ceramic substrate layer and N fluorescent ceramic layers, wherein N is 1 to 3, the N fluorescent ceramic layers are sequentially stacked on the surface of the ceramic substrate layer, and the material of the ceramic substrate layer is MgAl 2 O 4 The material of the fluorescent ceramic layer is fluorescent powder.
[0007] Furthermore, the thickness of the ceramic substrate layer is 0.3 mm to 1.0 mm.
[0008] Furthermore, the thickness of each fluorescent ceramic layer is 0.1 mm to 0.3 mm, and the fluorescent powder is at least one of yellow fluorescent powder, red fluorescent powder and green fluorescent powder.
[0009] The second object of the present invention is to provide a method for preparing the above-mentioned layered composite fluorescent ceramic sheet, comprising the following steps:
[0010] MgAl 2 O 4 The powder is pressed to obtain a ceramic substrate layer precursor;
[0011] The sintering aid is added to the phosphor, and then stacked and laid on the surface of the ceramic substrate layer precursor in sequence, and spark plasma sintering is performed at 1250° C. to 1550° C. to obtain a layered composite fluorescent ceramic sheet.
[0012] Furthermore, during the spark plasma sintering process, the temperature is first raised to 1100°C at a rate of 100°C / min, then raised to a sintering temperature of 1250°C to 1550°C at a rate of 5°C / min to 50°C / min, kept at that temperature for 5min to 20min, then dropped to 800°C at a rate of 50°C / min, and then cooled to room temperature.
[0013] Furthermore, during the spark plasma sintering process, the pressure is 50MP to 100MPa.
[0014] Furthermore, the amount of the sintering aid is 0.1 wt.% to 1.1 wt.% of the total mass of the phosphor.
[0015] Furthermore, the sintering aid is LiF, La 2 O 3 , CaO or at least one of the above.
[0016] The third object of the present invention is to provide a light-emitting device, comprising the above-mentioned layered composite fluorescent ceramic sheet and a light-emitting chip, wherein the layered composite fluorescent ceramic sheet is used as a light-transmitting material for a shell package, or as a light-emitting material arranged on the excitation surface of the light-emitting chip.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) The present invention uses MgAl 2 O 4 The powder is used as a ceramic substrate layer, and fluorescent ceramic layers are stacked on the ceramic substrate layer in sequence to form a layered composite fluorescent ceramic sheet. Compared with the traditional fluorescent glass sheet, MgAl 2 O 4 The refractive index difference between transparent ceramic and phosphor is small, which can improve the transmittance and thus the luminous efficiency. On the other hand, for high-power LED, the temperature generated by the chip will reach 150℃~200℃, which will directly lead to the temperature quenching effect of the fluorescent material on the chip, causing the packaged LED device to be prone to light decay, color temperature deviation, and greatly shortened life. 2 O 4 Transparent ceramic substrates have high thermal conductivity and refractive index and strong thermal stability, which can solve the problems of heat dissipation and light conversion efficiency at the same time, thereby increasing the operating current and further improving the luminous intensity and stability of high-power LEDs.
[0019] (2) The layered composite fluorescent ceramic sheet prepared by the present invention has high hardness, which can make the device more wear-resistant and impact-resistant. After long-term use, the surface damage is less, the transmittance is maintained at a high level, and the service life of the LED is longer.
[0020] (3) The present invention performs discharge plasma sintering on a ceramic substrate layer precursor, so that the phosphor still retains the fluorescence conversion performance after high-temperature sintering. By adjusting the thickness of the fluorescent ceramic layer, white light with different color temperatures and color coordinates can be generated. After being made into fluorescent transparent ceramics, not only can the optical transmittance be improved, but it can also be resistant to high temperatures, have stable performance, and have a long storage time, which greatly facilitates the packaging production process and avoids the problem of controlling the uniformity of the existing coating after the phosphor is mixed with epoxy resin / silicone. Compared with the existing phosphor coating process, the use of fluorescent transparent ceramics to make white light LEDs has the advantages of fewer process flows, simple production process, and lower cost, which is conducive to the large-scale promotion and application of LED products. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the assembly process of the mold when sintering the layered composite fluorescent ceramic sheet of the present invention.
[0022] Figure 2 This is a cross-sectional view of the layered composite fluorescent ceramic sheet of the present invention.
[0023] Figure 3 MgAl prepared in Example 1 of the present invention 2 O 4 Transmittance graph and actual image of the transparent ceramic substrate layer alone.
[0024] Figure 4 The transmittance and physical picture of the layered composite fluorescent ceramic sheet prepared in Example 1 of the present invention.
[0025] Figure 5 It is a schematic structural diagram of the light emitting device of the present invention.
[0026] Figure 6 This is a physical picture of the light emitting device of the present invention.
[0027] Figure 7 This is a graph showing the electroluminescent performance of a light-emitting device formed by a layered composite fluorescent ceramic sheet according to Example 1 of the present invention. Figure 7 In the figure, a is the electroluminescence spectrum of the layered composite fluorescent ceramic sheet after being connected to a DC power supply, and b is the color temperature-color coordinate diagram.
[0028] Figure 8 This is a graph showing the electroluminescent performance of a light-emitting device formed by a layered composite fluorescent ceramic sheet according to Example 2 of the present invention. Figure 8 In the figure, a is the electroluminescence spectrum of the layered composite fluorescent ceramic sheet after being connected to a DC power supply, and b is the color temperature-color coordinate diagram. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0031] For high-power LEDs, the key to improving LED life is to use packaging materials with fast heat dissipation and high thermal stability. Fluorescent glass has great advantages in preparation cost, large-scale production and color expansion, but its thermal conductivity is low (about 1W·m -1 ·K -1) is prone to luminescence saturation at low power density, and the refractive index of the glass matrix (about 1.5) does not match the refractive index of YAG:Ce (about 1.84), resulting in low transparency and poor optical performance of the material.
[0032] Based on the above problems, on the one hand, the present invention provides a layered composite fluorescent ceramic sheet, the layered composite fluorescent ceramic sheet comprises a ceramic substrate layer and N fluorescent ceramic layers, wherein N is 1 to 3, the N fluorescent ceramic layers are sequentially stacked on the surface of the ceramic substrate layer, and the material of the ceramic substrate layer is MgAl 2 O 4 The material of the fluorescent ceramic layer is fluorescent powder.
[0033] The present invention uses MgAl 2 O 4 The transparent ceramic material is used as the substrate layer, with a refractive index of about 1.71, which is much higher than glass, and has high light extraction efficiency (the light extraction efficiency can be increased by nearly 30%). 2 O 4 Transparent ceramics are light-transmitting and, as shown in Table 1, are more resistant to high temperatures and have a higher thermal conductivity (14.9W / m·K to 17.0W / m·K) than materials such as resin and glass, which is beneficial for reducing the operating temperature of fluorescent materials, thereby reducing chip temperature, increasing operating current, and further enhancing the stability and luminous intensity of high-power LEDs. Based on this, the present invention adopts MgAl 2 O 4 Transparent ceramic is used as a substrate. Multiple fluorescent ceramic layers are stacked in sequence on a transparent ceramic substrate layer to form a layered composite fluorescent ceramic sheet, which provides a new solution for the fluorescence conversion and packaging of white light LEDs.
[0034] Table 1 Physical properties of packaging materials
[0035] Material Thermal conductivity (W / m·k) Refractive Index Silicone 0.08~0.3 1.4 Epoxy resin 0.2~0.3 1.4 Glass 0.4~1.4 1.5 MgAl2O4 transparent ceramics 14.9~17 1.71
[0036] It should be noted that the MgAl 2 O 4 The powder size is nanometer-level, and the phosphor is micrometer-level. The size difference is large. Direct compounding will lead to serious surface light scattering, resulting in light loss and reduced luminous efficiency. Therefore, the present invention uses MgAl 2 O 4 The powder is used as a ceramic substrate layer, and fluorescent ceramic layers are stacked on the ceramic substrate layer in sequence to form a layered composite fluorescent ceramic sheet. Compared with the traditional fluorescent glass sheet, MgAl 2 O 4The refractive index difference between transparent ceramic and phosphor is small, which can improve the transmittance and thus the luminous efficiency. On the other hand, for high-power LED, the temperature generated by the chip will reach 150℃~200℃, which will directly lead to the temperature quenching effect of the fluorescent material on the chip, causing the packaged LED device to be prone to light decay, color temperature deviation, and greatly shortened life. 2 O 4 Transparent ceramics have higher thermal conductivity than glass and dissipate heat faster, which can reduce the impact of high temperature on the performance of light-emitting devices. It can solve the problems of heat dissipation and light conversion efficiency at the same time, thereby increasing the working current and further improving the luminous intensity and stability of high-power LEDs. The prepared layered composite fluorescent ceramic sheet has high hardness, which can make the device more wear-resistant and impact-resistant. After long-term use, the surface is less damaged, and the high transmittance is maintained, which prolongs the service life of high-power LEDs.
[0037] In a specific embodiment, the thickness of the ceramic substrate layer is 0.3 mm to 1.0 mm. In a preferred embodiment, the thickness of the ceramic substrate layer is 0.4 mm. It should be noted that if the ceramic substrate layer is too thick, the optical transmittance of the ceramic will decrease and the light extraction efficiency will decrease.
[0038] In a specific embodiment, the thickness of each fluorescent ceramic layer is 0.1 mm to 0.3 mm, and the fluorescent powder is at least one of yellow fluorescent powder, red fluorescent powder, and green fluorescent powder. In a preferred embodiment, the thickness of each fluorescent ceramic layer is 0.1 mm. It should be noted that the thickness of the fluorescent ceramic layer, on the one hand, affects the transmittance of the ceramic. Too thick a thickness will cause the transmittance of the ceramic to decrease. On the other hand, it can adjust the color temperature, color coordinates, color rendering index, etc., so that it can be applied to different scenes.
[0039] On the other hand, the present invention provides a method for preparing the above-mentioned layered composite fluorescent ceramic sheet, comprising the following steps:
[0040] S1、MgAl 2 O 4 The powder is pressed to obtain a ceramic substrate layer precursor.
[0041] S2. Add a sintering aid to the phosphor, and then stack and lay it on the surface of the ceramic substrate layer precursor in sequence, and perform spark plasma sintering at 1250° C. to 1550° C. to obtain a layered composite fluorescent ceramic sheet.
[0042] It should be noted that the purpose of the present invention is to produce a layered composite transparent fluorescent ceramic sheet with high process reliability and excellent optical performance to replace the fluorescent glass sheet packaging. Due to the large size difference between the yellow phosphor and the transparent ceramic powder, there are more direct composite backscattering centers, which may lead to a decrease in light conversion efficiency and a decrease in the lumen efficiency of the prepared white light LED. Therefore, the present invention proposes a method for packaging white light LEDs with layered composite fluorescent ceramics, that is, the phosphor is combined with MgAl 2 O 4 The powders are stacked into different layers, and double-layer or multi-layer composite fluorescent ceramics are prepared by spark plasma sintering (SPS). Compared with the white light LED devices of glass phosphor package (PiG), this method can not only improve the optical transmittance, but also withstand high temperature, and can provide a low-cost packaging method for high-power white light LEDs in industrial production.
[0043] The present invention performs discharge plasma sintering on a ceramic substrate layer precursor, and the fluorescent powder still retains the fluorescent conversion performance after high-temperature sintering. By adjusting the thickness of the fluorescent ceramic layer, white light with different color temperatures and color coordinates can be generated. After being made into fluorescent transparent ceramics, not only the optical transmittance can be improved, but also the high temperature resistance, stable performance and long storage time can be achieved, which greatly facilitates the packaging production process and avoids the problem of uniformity control of glue coating after the existing fluorescent powder is mixed with epoxy resin / silicone. Compared with the existing fluorescent powder coating process, the use of fluorescent transparent ceramics to make white light LEDs has the advantages of fewer process flows, simple production process and lower cost, which is conducive to the large-scale promotion and application of LED products.
[0044] In a specific embodiment, during the spark plasma sintering process, the temperature is first increased to 1100°C at a rate of 100°C / min, then increased to a sintering temperature of 1250°C to 1550°C at a rate of 5°C / min to 50°C / min, kept at that temperature for 5min to 20min, then decreased to 800°C at a rate of 50°C / min, and then cooled to room temperature.
[0045] In a specific embodiment, during the spark plasma sintering process, the pressure is 50 MPa to 100 MPa.
[0046] In a specific embodiment, the amount of the sintering aid is 0.1 wt.% to 1.1 wt.% of the total mass of the phosphor.
[0047] In a specific embodiment, the sintering aid is LiF, La 2 O 3 , CaO or at least one of the above.
[0048] In addition, the present invention also provides a light-emitting device, including the above-mentioned layered composite fluorescent ceramic sheet, wherein the layered composite fluorescent ceramic sheet is used as a light-transmitting material for a shell package, or as a light-emitting material arranged on the excitation surface of a light-emitting chip.
[0049] The layered composite fluorescent ceramic sheet ceramic material of the present invention can be used as both a fluorescent luminescence conversion material and a packaging material, eliminating the glue coating process and avoiding the problem of glue coating uniformity control. Compared with the existing fluorescent powder coating process, the cost is low, the process is less, and the production process is simple, which is conducive to large-scale promotion and application. The application of transparent fluorescent ceramics fully utilizes the excellent optical, thermal and mechanical properties of transparent ceramic materials, significantly improves the performance and service life of LEDs, and will greatly expand the application field of LEDs.
[0050] Among them, when the layered composite fluorescent ceramic sheet is used as the light-transmitting material for the shell package, the transparent ceramic matrix has high thermal conductivity, so the heat dissipation is fast. Under the condition of constant current, the temperature rise is small, the LED's luminous wavelength and luminous intensity change little, and the luminous intensity can be increased by increasing the working current; the transparent ceramic matrix is resistant to high temperature and the transmittance can reach more than 80%, thereby reducing the luminous loss of the LED, allowing the device to be used in high temperature environments with a long service life; the transparent fluorescent ceramic has good mechanical properties, high hardness, wear resistance, and impact resistance. After long-term use, the surface damage is less, and the high transmittance can be maintained, with a long service life.
[0051] When the layered composite fluorescent ceramic sheet is used as a luminescent material and is arranged on the excitation surface of the light-emitting chip, the luminescent performance of the fluorescent ceramic is better than that of the fluorescent powder and has better uniformity, thereby improving the luminescent performance of the LED device; according to the wavelength characteristics of the blue light or purple light LED chip used, the appropriate type or ratio of the fluorescent powder can be selected to obtain different light outputs; the assembly direction of the layered composite fluorescent ceramic sheet and the LED chip can also be changed to adjust the performance parameters.
[0052] The invention is further described below through specific examples.
[0053] Example 1
[0054] This embodiment provides a method for preparing a layered composite fluorescent ceramic sheet, comprising the following steps:
[0055] S1. Weigh a certain amount of MgAl 2 O 4 The powder is placed in a graphite mold and dry pressed into shape. 2 O 4 The purity of the powder is 99.99%, and a ceramic substrate layer precursor is obtained. The ceramic substrate layer precursor has a diameter of 15 mm and a thickness of 3 mm to 6 mm. After sintering, it is about 1 mm and can be ground and polished to a thickness of 0.5 mm.
[0056] S2, adding sintering aid CaO to the yellow phosphor (Ce: YAG), wherein the doping amount of CaO is 0.35wt% of the mass of the yellow phosphor, to obtain a mixed powder, such as Figure 1 As shown, 0.4 g of the mixed powder is spread on the surface of the ceramic substrate layer precursor, the mold is assembled, and the powder is put into a spark plasma sintering furnace for sintering. The sintering process is as follows: first, the temperature is raised to 1100°C at 100°C / min, and then raised to a sintering temperature of 1450°C at 5°C / min, and kept warm for 10 minutes. During the whole process, a pressure of 65 MPa is applied, and then the temperature is reduced to 800°C at a rate of 50°C / min. Finally, the powder is cooled to room temperature with the furnace to obtain a crude layered composite fluorescent ceramic sheet with a thickness of 1.4 mm.
[0057] S2. The rough layered composite fluorescent ceramic sheet is coarsely ground with 180-mesh and 240-mesh diamond sandpapers in sequence, then finely ground with 600-mesh sandpaper, and then polished with 1200-mesh, 2000-mesh, 4000-mesh, and 8000-mesh sandpapers in sequence, and finally ground and polished to 0.8 mm to obtain a layered composite fluorescent ceramic sheet, wherein the ceramic substrate layer is 0.5 mm and the fluorescent layer is 0.3 mm. The actual picture of the prepared layered composite fluorescent ceramic sheet is as shown in FIG. Figure 2 shown.
[0058] Example 2
[0059] This embodiment provides a method for preparing a layered composite fluorescent ceramic sheet, comprising the following steps:
[0060] S1. Weigh a certain amount of MgAl 2 O 4 The powder is placed in a graphite mold and dry pressed into shape. 2 O 4 The purity of the powder is 99.99%, and a ceramic substrate layer precursor is obtained. The ceramic substrate layer precursor has a diameter of 15 mm and a thickness of 3 mm to 6 mm. After sintering, it is about 1 mm and can be ground and polished to a thickness of 0.5 mm.
[0061] S2, adding sintering aid CaO to the yellow phosphor (Ce: YAG), wherein the doping amount of CaO is 0.35wt% of the mass of the yellow phosphor, to obtain a mixed powder, such as Figure 1As shown, 0.4 g of the mixed powder is spread on the surface of the ceramic substrate layer precursor, the mold is assembled, and the powder is put into a spark plasma sintering furnace for sintering. The sintering process is as follows: first, the temperature is raised to 1100°C at 100°C / min, and then raised to a sintering temperature of 1450°C at 5°C / min, and kept warm for 10 minutes. During the whole process, a pressure of 65 MPa is applied, and then the temperature is reduced to 800°C at a rate of 50°C / min. Finally, the powder is cooled to room temperature with the furnace to obtain a crude layered composite fluorescent ceramic sheet with a thickness of 1 mm.
[0062] S3. The rough layered composite fluorescent ceramic sheet is coarsely ground with 180-mesh and 240-mesh diamond sandpapers in sequence, then finely ground with 600-mesh sandpaper, and then polished with 1200-mesh, 2000-mesh, 4000-mesh, and 8000-mesh sandpapers in sequence, and finally ground and polished to 0.6 mm to obtain a layered composite fluorescent ceramic sheet, in which the ceramic substrate layer is 0.5 mm and the fluorescent layer is 0.1 mm.
[0063] Example 3
[0064] This embodiment provides a method for preparing a layered composite fluorescent ceramic sheet, comprising the following steps:
[0065] S1. Weigh a certain amount of MgAl 2 O 4 The powder is placed in a graphite mold and dry pressed into shape. 2 O 4 The purity of the powder is 99.99%, and a ceramic substrate layer precursor is obtained. The ceramic substrate layer precursor is a body with a diameter of 15 mm and a thickness of mm to 6 mm, which is ground and polished to a thickness of 0.5 mm.
[0066] S2, yellow phosphor (Ce:YAG) and red phosphor (Y 2 O 3 :Eu) is added with a sintering aid LiF to obtain a mixed powder, wherein the amount of red phosphor is 1.5wt% of the mass of yellow phosphor, and the amount of LiF doped is 0.4wt% of the total mass of phosphor. Figure 1 As shown, 0.4 g of the mixed powder is spread on the surface of the ceramic substrate layer precursor, the mold is assembled, and the powder is put into a spark plasma sintering furnace for sintering. The sintering process is as follows: first, the temperature is increased to 1100°C at 100°C / min, and then increased to a sintering temperature of 1550°C at 5°C / min, and kept warm for 10 minutes. During the whole process, a pressure of 65 MPa is applied, and then the temperature is reduced to 800°C at a rate of 50°C / min. Finally, the powder is cooled to room temperature with the furnace to obtain a crude layered composite fluorescent ceramic sheet with a thickness of 1.2 mm.
[0067] S3. The rough layered composite fluorescent ceramic sheet is coarsely ground with 180-mesh and 240-mesh diamond sandpapers in sequence, then finely ground with 600-mesh sandpaper, and then polished with 1200-mesh, 2000-mesh, 4000-mesh, and 8000-mesh sandpapers in sequence, and finally ground and polished to 0.8 mm to obtain a layered composite fluorescent ceramic sheet, in which the ceramic substrate layer is 0.5 mm and the fluorescent layer is 0.3 mm.
[0068] Example 4
[0069] This embodiment provides a method for preparing a layered composite fluorescent ceramic sheet, comprising the following steps:
[0070] S1. Weigh a certain amount of MgAl 2 O 4 The powder is placed in a graphite mold and dry pressed into shape. 2 O 4 The purity of the powder is 99.99%, and a ceramic substrate layer precursor is obtained. The ceramic substrate layer precursor is a body with a diameter of 15 mm and a thickness of 3 mm to 6 mm. After sintering, it is about 1 mm and can be ground and polished to a thickness of 0.5 mm.
[0071] S2, yellow phosphor (Ce:YAG) and red phosphor (Sr, Ca)AlSiN 3 :Eu) is added with a sintering aid LiF to obtain a mixed powder, wherein the amount of red phosphor is 2.0wt% of the mass of yellow phosphor, and the amount of LiF doped is 0.35wt% of the total mass of phosphor. Figure 1 As shown, 0.4 g of the mixed powder is spread on the surface of the ceramic substrate layer precursor, the mold is assembled, and the powder is put into a spark plasma sintering furnace for sintering. The sintering process is as follows: first, the temperature is increased to 1100°C at 100°C / min, and then increased to a sintering temperature of 1550°C at 5°C / min, and kept warm for 10 minutes. During the whole process, a pressure of 50 MPa is applied, and then the temperature is reduced to 800°C at a rate of 50°C / min. Finally, the powder is cooled to room temperature with the furnace to obtain a crude layered composite fluorescent ceramic sheet with a thickness of 1.2 mm.
[0072] S3. The rough layered composite fluorescent ceramic sheet is coarsely ground with 180-mesh and 240-mesh diamond sandpapers in sequence, then finely ground with 600-mesh sandpaper, and then polished with 1200-mesh, 2000-mesh, 4000-mesh, and 8000-mesh sandpapers in sequence, and finally ground and polished to 0.8 mm to obtain a layered composite fluorescent ceramic sheet, in which the ceramic substrate layer is 0.5 mm and the fluorescent layer is 0.3 mm.
[0073] The MgAl prepared in Example 1 2 O 4The transparent ceramic substrate layer and the prepared layered composite fluorescent ceramic sheet were tested for performance, and the results are as follows:
[0074] Figure 3 MgAl prepared in Example 1 of the present invention 2 O 4 Transparent ceramic substrate layer individual transmittance diagram and actual image. Figure 3 As shown, MgAl 2 O 4 The theoretical transmittance of transparent ceramics is 86.7%, and the present invention can reach 77.7%. Figure 3 As shown in the small picture below the middle curve, the text below can be clearly seen from the actual picture, so light can easily pass through and it can be used as a substrate layer for luminescent materials.
[0075] Figure 4 The transmittance and physical picture of the layered composite fluorescent ceramic sheet prepared in Example 1 of the present invention. Figure 4 As shown, the transmittance in the visible light range can reach up to 65%. Figure 4 As shown in the small picture above the middle curve, the text below can be clearly seen from the actual picture, so light can easily pass through and it can be used as a substrate layer for luminescent materials.
[0076] The present invention also provides a light emitting device, such as Figure 5 As shown, the layered composite fluorescent ceramic sheet 1 prepared in Example 1, Example 2 or Example 3 is arranged on a 10W blue light integrated high-power LED chip 2, wherein the ceramic substrate layer of the layered composite fluorescent ceramic sheet 1 is in contact with the upper surface of the LED chip 2, and a heat dissipation substrate 3 with a combing structure is provided on the lower surface of the LED chip 2, to obtain a light-emitting device, and the actual picture of the light-emitting device is shown in FIG. Figure 6 Connect the DC regulated power supply to make it emit white light, and test the electroluminescent performance.
[0077] Figure 7 This is a graph showing the electroluminescent performance of a light-emitting device formed by a layered composite fluorescent ceramic sheet according to Example 1 of the present invention. Figure 7 a is the electroluminescence spectrum of the layered composite fluorescent ceramic sheet after the DC power supply is turned on, and b is the color temperature-color coordinate diagram. The luminescent color of the material can be evaluated according to the position of the luminescent peak, the color purity of the luminescent material can be reflected according to the spectrum width, and the luminescent color can also be adjusted by adjusting the ratio of the two luminescent peaks, such as Figure 7As shown in a, there are two luminous peaks. The peak around 454nn is blue light, and the peak around 554nm is yellow-green light. The two can be combined to form white light. After the blue light LED chip is powered on and emits blue light, part of the blue light is absorbed by the ceramic piece, and the other part passes through the ceramic piece and combines with the yellow light emitted by the phosphor to form white light. The color temperature value can judge the chromaticity quality of the light source, such as whether the light color is warm or cold, which determines the application scenario. The color coordinates can show the color characteristics of the luminescent material. Figure 7 It can be seen from b that when the light-emitting layer is thicker, less blue light is transmitted, so less blue light is compounded with yellow light. The final light is yellowish, with color coordinates of (0.3995, 0.4815) and a color temperature of 3986K. It can be used in more relaxing places.
[0078] Figure 8 This is a graph showing the electroluminescent performance of a light-emitting device formed by a layered composite fluorescent ceramic sheet according to Example 2 of the present invention. Figure 8 a in the figure is the electroluminescence spectrum of the layered composite fluorescent ceramic sheet after the DC power supply is turned on, and b is the color temperature-color coordinate diagram. Figure 8 As shown, the luminous layer is 0.1mm, so more blue light is transmitted, and the proportion of blue light combined with yellow light to form white light is higher. Therefore, the light is white, the color coordinates are (0.347, 0.3788), and the color temperature is 4980K. It can be used for lighting in factory workshops, etc.
[0079] The hardness test of the layered composite fluorescent ceramic sheet prepared in Example 3 was carried out, and the hardness of the layered composite fluorescent ceramic sheet was 16.3 GPa. A 10 W blue light integrated high-power LED chip was combined with the layered composite fluorescent ceramic sheet and connected to a DC regulated power supply to make it emit light. The test showed that the transmittance of the layered composite fluorescent ceramic sheet was 62%; the absolute quantum yield was 57.46%; the color coordinates were (0.4021, 0.4678), and the color temperature was 4035K.
[0080] The layered composite fluorescent ceramic sheet prepared in Example 4 and a 10W blue light integrated high-power LED chip are combined together and connected to a DC regulated power supply to make it emit light. The test shows that the transmittance of the layered fluorescent ceramic sheet is 58%; the absolute quantum yield is 50.84%; the color coordinates are (0.3245, 0.3287), and the color temperature is 5879K.
[0081] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0082] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A layered composite fluorescent ceramic sheet, characterized in that: The layered composite fluorescent ceramic sheet includes a ceramic substrate layer and N fluorescent ceramic layers, wherein N is 1 to 3, and the N fluorescent ceramic layers are sequentially stacked on the surface of the ceramic substrate layer. The material of the ceramic substrate layer is MgAl2O4, and the material of the fluorescent ceramic layer is fluorescent powder.
2. The layered composite fluorescent ceramic sheet according to claim 1, characterized in that: The thickness of the ceramic substrate layer is 0.3 mm to 1.0 mm.
3. The layered composite fluorescent ceramic sheet according to claim 1, characterized in that: The thickness of each fluorescent ceramic layer is 0.1 mm to 0.3 mm, and the fluorescent powder is at least one of yellow fluorescent powder, red fluorescent powder and green fluorescent powder.
4. A method for preparing a layered composite fluorescent ceramic sheet according to any one of claims 1 to 3, characterized in that: The following steps are involved: The MgAl2O4 powder is pressed to obtain a ceramic substrate layer precursor; The sintering aid is added to the phosphor, and then stacked and laid on the surface of the ceramic substrate layer precursor in sequence, and spark plasma sintering is performed at 1250° C. to 1550° C. to obtain a layered composite fluorescent ceramic sheet.
5. The method for preparing the layered composite fluorescent ceramic sheet according to claim 4, characterized in that: During the spark plasma sintering process, the temperature is first raised to 1100°C at a rate of 100°C / min, then raised to a sintering temperature of 1250°C to 1550°C at a rate of 5°C / min to 50°C / min, kept at that temperature for 5min to 20min, then dropped to 800°C at a rate of 50°C / min, and then cooled to room temperature.
6. The method for preparing the layered composite fluorescent ceramic sheet according to claim 4, characterized in that: During the spark plasma sintering process, the pressure is 50MP~100MPa.
7. The method for preparing the layered composite fluorescent ceramic sheet according to claim 4, characterized in that: The amount of the sintering aid is 0.1wt.% to 1.1wt.% of the total mass of the phosphor.
8. The method for preparing the layered composite fluorescent ceramic sheet according to claim 4, characterized in that: The sintering aid is at least one of LiF, La2O3, and CaO.
9. A light emitting device, characterized in that: The invention comprises the layered composite fluorescent ceramic sheet as claimed in any one of claims 1 to 3, wherein the layered composite fluorescent ceramic sheet is used as a light-transmitting material for a shell package, or is used as a luminescent material and arranged on an excitation surface of a luminescent chip.
Citation Information
Patent Citations
LED lamp based on remote fluorescent powder technology
CN104681695A
Preparation method of composite fluorescent ceramic
CN116813327A
Transmission-type three-layer composite structure fluorescent ceramic for laser illumination and preparation method of transmission-type three-layer composite structure fluorescent ceramic
CN117658637A
Manufacture of electroluminescence element
JP1993082258A